Improving Critical Thinking Skills of Vocational School Students Using Problem-Based Learning - Kharismaputra, Aulia Prima; Santoso, Sigit; Murwaningsih, Tri (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine the differences in critical thinking skills between students who learn using the problem based learning model and STAD model. This research is a quantitative study with a quasi-experimental method. The population of this study is the X grade students of SMK Negeri 3 Surakarta in the academic year 2017/2018. Samples were obtained by using cluster random sampling technique consisting of two classes namely X PM 1 class as the experimental class with problem-based learning and X PM 3 class as the control class with STAD learning. The technique of collecting data uses a multiple choice test to determine students' critical thinking skills. Data Analysis is using MANOVA. The results of the study indicate that there is a significant influence between the learning model on critical thinking skills. The application of the problem-based learning model proved to be more able to improve students' critical thinking skills compared to the STAD learning model.